Development of method of analysis of isotopes methane modifications; Korus 2004; V. 2 - Vlasov V. A. Viktor Alekseevich (2004, 2004)
Happens to a synopsis of methods and equipments for the remote analysis of surges of different hydrocarbons. On base of analysis given is offered remote method of analysis of isotopes methane modifications